Protein C Pathway in Paediatric and Neonatal Sepsis - Eliwan, Hassan; Omer, Murwan; McKenna, Ellen; Kelly, Lynne A.; Nolan, Beatrice; Regan, Irene; Molloy, Eleanor J. (Frontiers in Pediatrics, 2022)
Protein C plays a major role in the physiological regulation of coagulation pathways through inactivation of factor Va, factor VIIIa, and plasminogen activator inhibitor. Protein C is involved in the control of inflammation during sepsis, by inhibiting release of pro-inflammatory cytokines, thereby controlling neutrophil, and monocyte effects on injured tissue. Recombinant human activated protein C (rhAPC) reduced mortality in adult sepsis in earlier studies but had no significant benefit in more recent trials. Protein C levels are reduced during pediatric and neonatal sepsis, which may play a major role in the development of disseminated intravascular thrombosis, purpura fulminans, and multiorgan dysfunction. The role of protein C in pediatric sepsis requires further clinical and immunological evaluation to define the patient subgroups who may benefit from this therapy. Newer versions of rhAPC are under development with less risk of haemorrhage potentially broadening the scope of this intervention.